The Relationship between Intensive Care Unit's Nurses' Informatics Competency and Quality of Patients' Electronic Health Record's Documentation - Laila Akhu-Zaheya; Mohammad Etoom (Jordan University of Science and Technology, 2024)
Background: Nursing Informatics (NI) and the development and growth of Health Information Technology (HIT) are becoming a necessary part of all aspects of the nursing practice, especially in critical care settings. In addition, researchers agree on using standardized and electronic documentation to support the nursing process and promote nursing documentation quality. Purpose: To examine the relationship between Intensive Care Unit Nurses' Informatics Competency and Quality of Patients' Electronic Health Record Documentation. Method: A descriptive, correlational, retrospective, cross-sectional design was used. Three hospitals that implemented the Electronic Health Records (EHRs) system were included in this study, using non-probability convenience sampling technique to recruit a total of 176 nurses. The nursing informatics competency was measured by the Self-Assessment of Nursing Informatics Competencies Scale (SANICS). The Quality of Electronic Health Record Documentation was assessed by the Audit instrument for nursing care plans in the patient record (Cat-ch-Ing). Descriptive and Inferential statistics were utilized to answer research questions. Results: The overall mean informatics competency score among nurses was 2.49 (SD = .73), with most of the nurses (81.79%) reporting a low competency score of less than three. The highest percentage of participants 29.4% (n = 52) have moderate quality of EHR documentation. Also, personal and clinical related characteristics accounts for 93.7% of the variance in quality of patients’ electronic health record documentation (R2 = .937, F = 8.707, p = .004). Once nursing informatics competency were entered into the model R2 still the same, making a total explained variance 93.7% (R2 = .937, F = 6.907, p = .013). Conclusion: The present study revealed low levels of nursing informatics competency among nurses, and the highest percentage of participants have moderate quality of EHR documentation. In addition, personal and clinical related characteristics accounts for 93.7% of the variance in quality of patients’ electronic health record documentation Implication to Nursing: This study provides evidence to guide nursing leaders, supervisors and policymakers in their planned actions and policies to support nursing capacity, nursing education, and nursing practice in the area of nursing informatics and electronic nursing documentation.